THE APPLICATION OF VARIOUS TYPES OF SLURRY AND DIFFERENT SOIL WATER CONTENT TO THE GROWTH AND YIELD OF Stylosanthesguianensis - I K., Suwartama; Trisnadewi, A. A. A. S.; Duarsa, M. A. P. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
The researchhas been to know the effect of various types of slurry and different soil water content and interaction to the growth and yield of Stylosanthes guianensis for 10 weeks at glass house research station of Animal Husbandry Faculty, Udayana University. Randomize block design was used in this experiment with split plot pattern. The main plot was type of slurry (cattle slurry , pig slurry and cattle bio-slurry ) and the sub plot was soil water content {100% field capacity (FC) 85% FC, 70% FC, and 55%FC)}, therefore were 12 treatment combinations Per each unit of treatment repeated 3 times. Variables observed were plant height increase, number of leave increase, number of stern increase, dry weight of leaves, stem, root and total of forage, dry weight of leaves and stem ratio, dry weight of total forage and root, and leaves area. Results of the experiment showed that does not significantly interaction between type of slurry with high moisture content of the soil. To factors that type of slurry was not significantly different except on number of stern increase. Soil water content was not significantly different except on the increase of plant height, stem and total forage dry weight and dry weight of leaves and stem ratio. Based on the variables of the experiment, it could be concluded does not interaction between type of slurry and soil water content at all variables. That types of slurry was not significantly different, however cattle bio-slurry tend to give the highest result. Soil water content until 55% FC gave no affect both in growth and yield of Stylosanthes guianensis. Keywords: type of slurry, soil wter content, growth, Stylosanthes guianensis